Movement and Protection for Random Shape Rockfalls in Steeply Dipping Coal Seams - Ming Liu; Jie Chen (Advances in Civil Engineering)
In view of the randomness of rockfalls shape and irregularity of the bottom floor of working face in steeply dipping coal seams (SDCS), it is difficult to accurately simulate rockfall movement, and it is consequently unable to effectively protect against multirockfalls. Therefore, a method for generating random shape rockfalls based on ellipsoid equation is proposed, and a 3D grid model of real bottom floor of working face is established based on the geographic information system data. In order to verify the accuracy and feasibility of the method and 3D model, the trajectory simulated by Rockyfor3D software is compared, and the proposed method and 3D model prove to be effective in simulating rockfall movement more accurately. Then the proposed method and 3D grid model are applied to solve the problem of multirockfalls protection in numerical simulation, and the main factors affecting the structural stress response of protective netting are analyzed by taking three incident modes of parallel heights, ladder parallel, and the same trajectory. In the simulation, it is found out that the trajectory of irregular rockfalls is greatly affected by the shape of rockfall and working face floor; during the process of multiple rockfalls colliding with the protective netting, the peak stress on the protective netting is inversely proportional to both the time interval between each rockfall and the distance between each rockfall. The findings presented in this research contribute to rockfall prediction and protection against rockfall hazards.